Forensic ballistics - Barreda, Ariel Barco (Quezon City : Wisemans Books Trading, 2021)
"This book in forensic ballistics explain the historical foundations of firearms identification mainly concerned with determining whether a bullet or cartridge was fired by a particular weapon, This book gives emphasis on the study of ammunitions, projectiles, gunpowder, primer and explosives, firearm, including the use of the bullet comparison microscope."
Includes references.
English text.
Keywords: Forensic ballistics